2016
DOI: 10.1002/jmri.25560
|View full text |Cite
|
Sign up to set email alerts
|

MR spectroscopy of breast cancer for assessing early treatment response: Results from the ACRIN 6657 MRS trial

Abstract: Purpose To estimate the accuracy of predicting response to neoadjuvant chemotherapy (NACT) in patients with locally advanced breast cancer using magnetic resonance spectroscopy (MRS) measurements made very early in treatment. Materials and Methods This prospective HIPAA-compliant protocol was approved by the American College of Radiology and local-site institutional review boards. 119 women with invasive breast cancer of ≥3 cm undergoing NACT were enrolled between September 2007 and April 2010. MRS measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(107 citation statements)
references
References 35 publications
(44 reference statements)
0
41
0
Order By: Relevance
“…These focuses have included: unedited, short-TE MRS (Deelchand et al, 2015); low-field MRS (Träber et al, 2006); ultra-high field MRS (van de Bank, 2015); absolute quantification (Bovée et al, 1998; De Beer et al, 1998; Keevil et al, 1998; Soher et al, 1996); MRSI (Sabati et al, 2015; Wijnen et al, 2010); body MRS (Bolan et al, 2016; Scheenen et al, 2011); brain tumor classification (García-Gómez et al, 2009; Julià-Sapé et al, 2006; Tate et al, 2003; Vicente et al, 2013); and HIV-associated dementia (Chang et al, 2004; Lee et al, 2003; Sacktor et al, 2005). Even for short-TE methods, the degree of agreement between sites and scanners is highly dependent on the degree of acquisition homogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…These focuses have included: unedited, short-TE MRS (Deelchand et al, 2015); low-field MRS (Träber et al, 2006); ultra-high field MRS (van de Bank, 2015); absolute quantification (Bovée et al, 1998; De Beer et al, 1998; Keevil et al, 1998; Soher et al, 1996); MRSI (Sabati et al, 2015; Wijnen et al, 2010); body MRS (Bolan et al, 2016; Scheenen et al, 2011); brain tumor classification (García-Gómez et al, 2009; Julià-Sapé et al, 2006; Tate et al, 2003; Vicente et al, 2013); and HIV-associated dementia (Chang et al, 2004; Lee et al, 2003; Sacktor et al, 2005). Even for short-TE methods, the degree of agreement between sites and scanners is highly dependent on the degree of acquisition homogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vivo MRS studies 24,71,78,79 have also reported that the water-to-fat ratio in invasive ductal carcinomas was higher compared with that in benign lesions or normal breast parenchyma. The water-to-fat ratio was also shown to be useful for monitoring the response of breast cancer to neoadjuvant chemotherapy.…”
Section: Differentiation Of Malignant Lesions From Benign Lesions Usimentioning
confidence: 99%
“…As in the diagnostic setting, factors such as poor shimming of the magnetic field, patient motion, and even the presence of gadolinium contrast can limit metabolic quantitative measurements for assessing treatment response …”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular the levels of PCho appear to increase during cell proliferation . For these reasons the tCho signal was explored as biomarker to monitor response to therapy …”
Section: Introductionmentioning
confidence: 99%